"How do we learn about sex?". Issue 1 (27th May 2014) - F. Preston, Lesley
Abstract : Purpose: – Using sex education at Shepparton South Technical School (South Tech) as a prism, the purpose of this paper is to analyse the Victorian Technical Schools Division policies and practices during the 1970-1980s. Design/methodology/approach: – The paper draws on a documented history of South Tech by using a blended methodology consisting of interviews, media-centred debates and a range of documentary sources. Findings: – The Technical Director, Edward "Ted" Jackson's 1970 policy empowered principals as educational leaders, in partnership with their community, to develop courses responding to student needs. This paper analyses a controversy concerning sex education in 1980 that brought such courses under the scrutiny of the Victorian public. Social implications: – Identifying the policies and practices of a sex education course that proved successful in the past enhances the development of contemporary courses. Originality/value: – Victoria's former secondary technical schools provide an important insight into current social and vocational problems.